PENGARUH AKTIVITAS BELAJAR SISWA DALAM PENERAPAN MODEL PROJECT BASED LEARNING BERBASIS SAINTIFIK TERHADAP HASIL BELAJAR PADA MATA PELAJARAN AKUNTANSI - Lulu Rahayu (Edulead : Journal of Education Management, 2019)
This study uses a single-subject experimental method, where the researcher only applies a project-based learning model to one class (single subject). The purpose of this study was to determine student activities, student learning outcomes, and to determine whether there was a significant influence between student activities in learning activities with project based learning models on student learning outcomes in cognitive and psychomooric aspects (skills) accounting. The research subjects were students of class X Accounting 4 SMK Negeri 1 Kedawung Cirebon Regency for the 2019/2020 academic year as many as 41 students. How to collect data in this study using student learning activity data through observation sheets, pretest and posttest scores, and student worksheets. Data analysis was carried out using quantitative descriptive analysis techniques using simple regression analysis (test) to determine the effect of student activities using project-based learning models on student learning outcomes in accounting subjects which were divided into cognitive, psychomotor, and both aspects of learning outcomes. the. How to collect data in this study using student learning activity data through observation sheets, pretest and posttest scores, and Student Worksheets. Analyzed by analysis (test) simple regression. Based on the results of the study obtained the value of student learning activities with an average of 81.76 with a good relationship level. Learning outcomes of cognitive and psychomotor aspects with an average of 83.46 with good criteria. After performing regression analysis, the value of sig < 0.05 was obtained so that there was a significant influence between student learning activities using the project based learning model on accounting learning outcomes with a coefficient of determination of 56.4%. So, the conclusion of this study is that student learning activities in the application of scientific-based project-based learning models have a significant effect on student learning outcomes in Accounting subjects on the subject of processing service company financial statements in class X Accounting 4 SMK Negeri 1 Kedawung, Cirebon Regency. Abstrak Penelitian ini menggunakan metode eksperimen subjek tunggal, dimana peneliti hanya menerapkan model pembelajaran berbasis proyek (project based learning) kepada satu kelas (subjek tunggal). Tujuan penelitian ini adalah untuk mengetahui aktivitas siswa, hasil belajar siswa, dan untuk mengetahui apakah terdapat pengaruh yang signifikan antara aktivitas siswa dalam kegiatan pembelajaran dengan model project based learning terhadap hasil belajar siswa dalam aspek kognitif dan psikomoorik (keterampilan) akuntansi. Subjek penelitian adalah siswa kelas X Akuntansi 4 SMK Negeri 1 Kedawung Kabupaten Cirebon Tahun Pelajaran 2019/2020 sebanyak 41 siswa. Cara pengambilan data dalam penelitian ini dengan menggunakan data aktivitas belajar siswa melalui lembar observasi, nilai pretest dan posttest, serta lembar kerja siswa. Analisis data dilakukan dengan menggunakan teknik analisis deskriptif kuantitatif dengan menggunakan analisis (uji) regresi sederhana untuk mengetahui pengaruh antara aktivitas siswa dengan menggunakan model pembelajaran berbasis proyek terhadap hasil belajar siswa pada mata pelajaran akuntansi yang dibedakan menjadi hasil belajar aspek kognitif, psikomotorik, dan kedua aspek tersebut. Cara pengambilan data dalam penelitian ini dengan menggunakan data aktivitas belajar siswa melalui lembar observasi, nilai pretest dan posttest, serta Lembar Kerja Siswa. Dianalisis dengan analisis (uji) regresi sederhana. Berdasarkan hasil penelitian diperoleh nilai aktivitas belajar siswa dengan rata-rata 81,76 dengan tingkat hubungan baik. Hasil belajar aspek kognitif dan psikomotorik dengan rata-rata 83,46 dengan kriteria baik. Setelah melakukan analisis regresi diperoleh nilai sig < 0,05 sehingga terdapat pengaruh yang signitifikan antara aktivitas belajar siswa dengan menggunakan model project based learning terhadap hasil belajar akuntansi dengan koefisien determinasi sebesar 56,4%. Jadi, simpulan penelitian ini adalah aktivitas belajar siswa dalam penerapan model project based learning berbasis saintifik berpengaruh signifikan terhadap hasil belajar siswa pada mata pelajaran Akuntansi pada pokok bahasan pemrosesan laporan keuangan perusahaan jasa di kelas X Akuntansi 4 SMK Negeri 1 Kedawung Kabupaten Cirebon.